DIVERGENCE OF THERMAL FACTORS OF TRACTION MACHINE ARMATURE WINDINGS UNDER HEAT TEST VIA BACK-TO-BACK METHOD - Afanasov, A. M. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2012)
Results of analysis of thermal processes in traction electric machines windings under their heat tests with a back-to-back method are presented. Analytical expressions are derived to allow specifying the degree of divergence of the tested machines armature windings thermal loads by values of their efficiency, specific power loss and relative deviation of their magnetic characteristics.